Penerapan Barcode Pada Perancangan Sistem Perangkat Lunak Bantu Penjualan Barang - Asep Syaputra; Ego Winanda (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2019)
The Barcode Based Software Sales Assistance Software System in Toko Ruly was built using the PHP programming language, and used the waterfall method as system development, with the stages of Communation, Planning, Modeling, Construction, and Deployment to facilitate the system development and use the Observation, Documentation Method , Interview and Literature Study for Data collection methods to support system development methods for designing these assistive software systems. Because there are many problems found, especially when recording goods data and then reports for monthly results, it is expected that the application of this assistive software can help the process of managing data on goods, goods reports, and sales transactions. From this research, we will get a barcode-based computerized system for sales and reporting systems that are better than the old system that uses a manual system. In the stages of testing this system directly uses the deployment technique to users related to the application of barcode-based assistive software systems in the Ruly Store